The Role of Noncoding RNA in Airway Allergic Diseases through Regulation of T Cell Subsets - Shenghao Cheng; Qingping Tang; Shaobing Xie; Sihui Wen; Hua Zhang; Zhihai Xie; Weihong Jiang (Mediators of Inflammation)
Allergic rhinitis and asthma are common airway allergic diseases, the incidence of which has increased annually in recent years. The human body is frequently exposed to allergens and environmental irritants that trigger immune and inflammatory responses, resulting in altered gene expression. Mounting evidence suggested that epigenetic alterations were strongly associated with the progression and severity of allergic diseases. Noncoding RNAs (ncRNAs) are a class of transcribed RNA molecules that cannot be translated into polypeptides and consist of three major categories, microRNAs (miRNAs), long noncoding RNAs (lncRNAs), and circular RNAs (circRNAs). Previous studies showed that ncRNAs were involved in the physiopathological mechanisms of airway allergic diseases and contributed to their occurrence and development. This article reviews the current state of understanding of the role of noncoding RNAs in airway allergic diseases, highlights the limitations of recent studies, and outlines the prospects for further research to facilitate the clinical translation of noncoding RNAs as therapeutic targets and biomarkers.